The issues of standardization of the quality management system - Karbaev N.K., Карбаев Н.К.; Nursultan I. , Нурсултан И. (Рroblems of engineering and professional education, 2022)
This international standard emphasizes that the condition for successful work on quality management is the application of statistical methods at all stages of the quality loop: in the analysis of the market, product design, determination of reliability requirements, durability and service life, process management, quality level determination, planning technical control, analysis of defects and evaluation of product performance. Of the statistical methods, experiment planning and factor analysis are the most often used; variance and regression analysis; safety assessment and risk analysis; quality control cards, selective statistical control, etc.